Pravāsanibandhakāra Bhoḷābhāī Paṭela - Khaḍadiyā, Maitreyī (Amadāvāda : Maitreyī Khaḍadiyā, 2014)
Study of travel writings of Bholābhāī Paṭela, Gujarati author and critic.
Includes bibliographical references (pages 125-126).
In Gujarati.
Keywords: Paṭela, Bholābhāī -- Criticism and interpretation; Travelers' writings, Gujarati -- History and criticism; Paṭela, Bholābhāī.; Travelers' writings, Gujarati; Criticism, interpretation, etc